Origin, causes and consequences of closed residential complexes in Valledupar-Colombia - Martínez-Barrios, Hermes E. (Prospectiva. Revista de Trabajo Social e Intervención Social, 2016)
This article has the objective to describe the origins, causes and consequences of closed residential complexes in the city of Valledupar. The methodological framework to be used in this project is oriented from the parameters of the qualitative approach (subjective and interpretive world), as well as the implementation of the research tradition of ethnography, within which we worked with the instruments of data collection as nonparticipant observation, participant observation and semi-structured interviews. The result being that some of the factors that have fueled booming (origin, causes and consequences) of this type of urban housing is the increased insecurity and urban violence and the absence of local government as a guarantor of the local public security; the growing spread in the city of sense of community; the growth of social dissent and increasing margin between the poor and the wealthy, adding the desire to achieve status and a degree of social balance in some social groups; aspiration to have contact with the environment and the desire of urban builders, a create a new urban trend, influenced by barranquillera society and in some cases the American way.